# Calculator search results

Formula
Solve the equation
Graph
$y = 2 x + 1$
$y = \dfrac { 1 } { 2 } x + 33$
$x$Intercept
$\left ( - \dfrac { 1 } { 2 } , 0 \right )$
$y$Intercept
$\left ( 0 , 1 \right )$
$x$Intercept
$\left ( - 66 , 0 \right )$
$y$Intercept
$\left ( 0 , 33 \right )$
$2x+1= \left( \dfrac{ 1 }{ 2 } \right) x+33$
$x = \dfrac { 64 } { 3 }$
 Solve a solution to $x$
$2 x + 1 = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ x } + 33$
 Calculate the multiplication expression 
$2 x + 1 = \color{#FF6800}{ \dfrac { x } { 2 } } + 33$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ \dfrac { x } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 33 }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 2 } = \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 66 }$
$4 x + 2 = \color{#FF6800}{ x } + 66$
 Move the variable to the left-hand side and change the symbol 
$4 x + 2 \color{#FF6800}{ - } \color{#FF6800}{ x } = 66$
$4 x \color{#FF6800}{ + } \color{#FF6800}{ 2 } - x = 66$
 Move the constant to the right side and change the sign 
$4 x - x = 66 \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ x } = 66 - 2$
 Organize the expression 
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } = 66 - 2$
$3 x = \color{#FF6800}{ 66 } \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
 Subtract $2$ from $66$
$3 x = \color{#FF6800}{ 64 }$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ 64 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 64 } { 3 } }$
 그래프 보기 
Graph
Solution search results